Current account determinants and external sustainability in periods of structural change - Sophocles N. Brissimis; George Hondroyiannis; Christos Papazoglou; Nicholas T. Tsaveas; Melina A. Vasardani (European Central Bank (ECB), 2010)
The aim of this paper is to study the main macroeconomic, financial and structural factors that shaped current account developments in Greece over the period from 1960 to 2007 and discuss these developments in relation to the issue of external sustainability. Concerns over Greece's external sustainability have emerged since 1999 when the current account deficit widened substantially and exhibited high persistence. The empirical model used, which theoretically rests on the intertemporal approach, treats the current account as the gap between domestic saving and investment. We examine the behaviour of the current account in the long run and the short run using co-integration analysis and a variety of econometric tests to account for the effect of significant structural changes in the period under review. We find that a stable equilibrium current account model can be derived if the ratio of private sector financing to GDP, as a proxy for financial liberalisation, is included in the specification. Policy options to restore the country's external sustainability are explored based on the estimated equilibrium model.
Keywords: F30; F32; 330; Current account model; external sustainability; Außenwirtschaftliches Gleichgewicht; Finanzmarktregulierung; Sparquote; Gleichgewichtsmodell; Kointegration; Griechenland